2007
DOI: 10.1038/sj.npp.1301641
|View full text |Cite
|
Sign up to set email alerts
|

Lower Phosphoinositide 3-Kinase (PI 3-kinase) Activity and Differential Expression Levels of Selective Catalytic and Regulatory PI 3-Kinase Subunit Isoforms in Prefrontal Cortex and Hippocampus of Suicide Subjects

Abstract: Phosphoinositide 3 (PI 3)-kinase is one of the key signaling enzymes that participates in a myriad of physiological functions in brain and is utilized by neurotrophins to mediate neuronal plasticity, cell survival, and inhibition of apoptosis for several neuronal subtypes. Our recent demonstration that expression of neurotrophic factors and activation of the receptor tyrosine kinase B are significantly altered in postmortem brain of suicide subjects led us to examine whether suicide brain is associated with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 82 publications
2
22
0
1
Order By: Relevance
“…Abnormalities in PI3K/Akt/GSK-3β pathway are implicated in depressive disorders. It has been demonstrated that the prefrontal cortex and hippocampus of suicide subjects with depression have a decreased activation of PI3K (Dwivedi et al, 2008). Furthermore, inhibition of GSK-3β has been reported to be associated with antidepressant effects (Beaulieu et al, 2008;Rosa et al, 2008) and GSK-3β inhibitors were reported to enhance the antidepressant-like effect of some antidepressant compounds (Budni et al, 2011;Moretti et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Abnormalities in PI3K/Akt/GSK-3β pathway are implicated in depressive disorders. It has been demonstrated that the prefrontal cortex and hippocampus of suicide subjects with depression have a decreased activation of PI3K (Dwivedi et al, 2008). Furthermore, inhibition of GSK-3β has been reported to be associated with antidepressant effects (Beaulieu et al, 2008;Rosa et al, 2008) and GSK-3β inhibitors were reported to enhance the antidepressant-like effect of some antidepressant compounds (Budni et al, 2011;Moretti et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Brain tissues from the same cohort have been used previously in various studies published by our group (Dwivedi et al, 2008; Dwivedi et al, 2009, 2010; Pandey et al, 2014). Dissected regions of interest included predominantly cortical gray matter.…”
Section: Methodsmentioning
confidence: 99%
“…Downstream second messenger signaling pathways involving mitogen-activated protein kinase/ERK (MEK)1, extracellular signal-regulated protein kinase (ERK)1/2, Raf-1, and B-Raf are altered in both animal models of depression and in the post-mortem brains of depressed suicide victims 2732. In addition, phosphoinositide 3 (PI-3)-kinase, protein kinase A (PKA), and protein kinase C (PKC) signaling all show depression-associated down-regulation 3336. Unsurprisingly, therefore, decreased activation of the downstream transcription factor cyclic adenosine monophosphate (cAMP) response element-binding (CREB) is a prominent feature in both post-mortem tissue and animal models of depression 37,38…”
Section: The Molecular Pathophysiology Of Depressionmentioning
confidence: 99%